2017
DOI: 10.1016/j.watres.2016.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of ammonia oxidizing bacteria and other members of nitrifying activated sludge communities to micropollutant biotransformation

Abstract: Improved micropollutant (MP) biotransformation during biological wastewater treatment has been associated with high ammonia oxidation activities, suggesting co-metabolic biotransformation by ammonia oxidizing bacteria as an underlying mechanism. The goal of this study was to clarify the contribution of ammonia oxidizing bacteria to increased MP degradation in nitrifying activated sludge (NAS) communities using a series of inhibition experiments. To this end, we treated a NAS community with two different ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 54 publications
4
76
3
2
Order By: Relevance
“…59 However, more recently, it has been found that acesulfame was degraded by activated sludge communities from different WWTPs. 50,60,61 Castronovo et al observed quantitative biotransformation of acesulfame to sulfamic acid and a metabolic degradation was hypothesized but the reaction pathway is not entirely understood yet. 60 We are not aware of any previous studies having demonstrated the observed dependence of acesulfame biotransformation on SRT.…”
Section: Dependence Of Biotransformation Rate Constants On Srtmentioning
confidence: 99%
“…59 However, more recently, it has been found that acesulfame was degraded by activated sludge communities from different WWTPs. 50,60,61 Castronovo et al observed quantitative biotransformation of acesulfame to sulfamic acid and a metabolic degradation was hypothesized but the reaction pathway is not entirely understood yet. 60 We are not aware of any previous studies having demonstrated the observed dependence of acesulfame biotransformation on SRT.…”
Section: Dependence Of Biotransformation Rate Constants On Srtmentioning
confidence: 99%
“…Hence, action of the AMO enzyme on any observed biotransformation of these compounds is highly unlikely. Other ammonia oxidizing enzymes (Helbling et al, 2010;Men et al, 2017) or heterotrophic bacteria (Fernandez Fontaina et al, 2016;Khunjar et al, 2011a) may be responsible for the biotransformation of TOrCs in aerobic activated sludge. For example, atenolol with a primary amide is known to undergo enzymatic hydrolysis to atenololic acid under aerobic conditions by amide hydrolyzing enzymes (e.g., amidase) that are abundant in activated sludge microbial communities (Radjenovic et al, 2008;Helbling et al, 2010).…”
Section: Impact Of Redox Condition On Biotransformationmentioning
confidence: 99%
“…For clomazone a typical laboratory half-life at 20 • C is 22.6 days (6.3-145.7 days) and its field half-life is 27.3 days (9.3-195 days) [24]. This wide spread in half-life values suggests that clomazone dissipation may be influenced by many factors, including UV irradiation [29], and the presence of oxygen [30] or ammonia-oxidizing bacteria [31]. In our study, the addition of the biological preparation shortened the dissipation half-lives by 6.3 days (7.1%) (experiment 1) and 18.4 days (25.1%) (experiment 2).…”
Section: Clomazonementioning
confidence: 99%